1990
DOI: 10.1002/anie.199014271
|View full text |Cite
|
Sign up to set email alerts
|

Doubly Bridged Prismanes, Dewar Benzenes and Benzene Derivatives from Cyclooctyne and 1, 8‐Cyclotetradecadiyne: En Route to Propella[n3]prismanes

Abstract: The highly strained Dewer‐benzene 1 and the prismane 2 can be obtained from Cyclooctyne in a few steps. 2 is formed by irradiation of 1 with long wavelength light; at λ = 250 nm only polymers are formed, presumably via the corresponding [5]paracyclophane.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
3
0

Year Published

1992
1992
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(4 citation statements)
references
References 16 publications
1
3
0
Order By: Relevance
“…In contrast, every molecule of this family with n Z 11 shows a less negative value for its HOMO energy. An increase in the value of the Ar 1 -Ch 1 -Ch 2 angle is noticed, where Ch 1 is an O atom in the O[n] family, from O [10] to O [11]. The last matches with the change in the trend observed in the HOMO energy profile of this family.…”
Section: Effect Of Chain Length On the Geometrical Central Ring Param...supporting
confidence: 67%
See 2 more Smart Citations
“…In contrast, every molecule of this family with n Z 11 shows a less negative value for its HOMO energy. An increase in the value of the Ar 1 -Ch 1 -Ch 2 angle is noticed, where Ch 1 is an O atom in the O[n] family, from O [10] to O [11]. The last matches with the change in the trend observed in the HOMO energy profile of this family.…”
Section: Effect Of Chain Length On the Geometrical Central Ring Param...supporting
confidence: 67%
“…Over the years, other synthetic pathways for the preparation of [n]paracyclophanes emerged, some of which were also based on the thermal and photochemical aromatization of Dewar's benzene derivatives. 10,11 It has been found that the stability of short-chain [n]paracyclophanes is strongly conditioned by n. Hence, [6]paracyclophane is isolable and stable at room temperature, [5]paracyclophane has only been observed in solution at room temperature, and [4]paracyclophane is observable only in an isolated matrix at very low temperatures. 12 In the case of the synthesis of [n]metacyclophanes (n = 6-8), several methods starting with thermal rearrangement have been proposed.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…1,2 This complex has been utilized extensively in the synthesis of substituted Dewar benzenes and tricyclo[4.2.0.0 0,0 ]oct-3-enes. [2][3][4][5] In almost all reported cases, the reacting partners are electron-deficient p-systems, such as acetylene dicarboxylic acid diesters. The accepted mechanism for this reaction is thermal [4p s +2p s ] cycloaddition between liberated cyclobutadiene and an electron-deficient 2p component.…”
mentioning
confidence: 99%